ANALISIS PERBEDAAN TINGKAT PROKRASTINASI DITINJAU DARI GENDER, SOCIO-PERSONAL, LOCUS OF CONTROL, SERTA KECERDASAN EMOSIONAL: Studi pada Mahasiswa Program Studi Manajemen FE UNJ - Handaru, Agung Wahyu; Sari Lase, Evi Permata; Paramita, Widya (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2014)
Two hundred and thirty twoundergraduate students of management major at State University of Jakarta were surveyed on their procrastination level, gender, socio-personal (parents’educationalbackground, number of siblings, university grade level), locus of control, and emotional intelligence. Result shows that 1) the procrastination level between male and female students is identical, 2) the procrastination levelbetween students whom his/her mother is holding university degree with other students whom his/her mother is not holding university degree is different,3) the procrastination level between studentswhom his/her father is holding university degree is different with other students whom his/her father is not holding university degree, 4) the procrastination level between students who have one sibling is different with other students who have more than one siblings, 5) the procrastination level between new students are different with senior students, 6) the procrastination level between students who have internal locus of control is different with other students who have external locus of control, 7)the procrastination level between students who have high emotional intelligence is different with otherstudents who have low emotional intelligence. Keywords: Procrastination, Gender, Socio-Personal, Locus of Control, Emotional Intelligence